The Roles of Masjid in Enhancing Networking Opportunities among the Muslims in the Era of Globalization - Badi, Jamal Ahmad; Surajudeen, Ahmad Tijani (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
Masjid or otherwise known as mosque is meant for tahānuth among the Muslims. By tahānuÏh, it refers to Muslims ‟ devotion in showing servitude and servility of obedience to Allah, the supreme Creator”. Masjid Qubā’ was the first mosque which the Prophet peace upon him laid its foundation. Islam gives prominence to three mosques: masjid al-Haram, masjid al-Nabawī and masjid al-Aqṣā. With the establishment of the masjid during the prophetic era, masjid played various roles such as spiritual, social, political, economic and more importantly it fostered networking opportunities among the disciples of the Prophet peace be upon him. Muslims meet in the masjid five times daily and once in a year in masjid al-Harām. Masjid is undeniably has a tendency of promoting the integration of all spheres of human affairs in the era of globalization. Unfortunately, the roles of masjid have been restricted to the spirituality whereby its inclusive role of networking opportunities has been fervently neglected in the era of globalization. Therefore, the primary aim and objective of this paper is to investigate and expand the role of masjid through the view-lens of networking opportunities among the contemporary Muslims in the era of globalization. In so doing, Muslims will maximize the opportunities of meeting in the masjid towards the enhancement of peaceful co-existence, unity, harmony. It is thereby recommended that, the management of masjid should provide a platform for promoting networking opportunities among the Muslims.